Hormonal responses and pregnancy outcomes after five-day ovulation synchronization and presynchronization programs in lactating dairy cows - Pulley, Stephanie Leeann (Kansas State University, 2014)
Two experiments assessed pregnancy outcomes (pregnancy per AI; P/AI) after 5-d Ovsynch-56 Resynch (RES; GnRH injection 5 d before [GnRH-1; d 0] and 56 h (GnRH-2) after the last PGF2α [PGF] injection on d 6 given 24 h after first PGF injection on d 5, and TAI on d 8) with and without a 5-d progesterone insert. In Exp. 1, only 76% of 1,023 nonpregnant cows enrolled on d 34 post-AI had high (≥1 ng/mL) progesterone. The RES-CIDR cows with low progesterone at treatment initiation had greater P/AI than RES-CON (37.7 vs. 29.4%), whereas RES-CIDR cows with high progesterone had lesser P/AI than RES-CON (27.4 vs. 34.3%) suggesting that supplemental progesterone is progesterone-dependent. In Exp. 2, 381 cows were enrolled in similar treatments on d 31 with RES on d 41post-AI plus a third treatment including PG-3-G (Pre-PGF on d 31, Pre-GnRH on d 34, and RES on d 41. The P/AI was similar among treatments but was greater in cows starting RES on d 41 when progesterone was low (44%) than high (33%).Experiment 3 determined LH and ovulatory responses in cows enrolled in two treatments before AI: 1) Pre10 (n = 37): PGF-1 and PGF-2 given 14 d apart (Presynch); or PG3G (n = 33): PGF given concurrent with the PGF-2, 3 d before GnRH-1 followed in 7 d by Ovsynch [injection of GnRH (GnRH-2) 7 d before PGF (PGF-3) and GnRH-3 at either 56 or 72 h after PGF-3] that was initiated 10 d after PGF-2 for Pre10 or 7 d after GnRH-1 of PG3G. The GnRH- 1 increased incidences of LH surges and ovulation in PG3G compared with Pre10. The LH in serum of Pre10 was greater than that of cows receiving PG3G after GnRH-2. Following GnRH- 3, cows receiving GnRH at 72 h had increased incidence of spontaneous LH surges before GnRH-3. The P/AI for PG3G vs. Pre10 and for 56 vs. 72 h was similar, but the Pre10-72 h treatment combination was less than all other treatment combinations. Release of LH is protocol dependent and flexibility of GnRH timing is an advantage for PG3G before first-service TAI.
Keywords: Lutenizing hormone; Estradiol; Ovsynch; Cosynch; Animal Sciences (0475)